Embryogenesis and plantlet formation in garlic Allium sativum L. - GREWAL, SUSHMA KOUL, MANJU SAMBYAL, S (Journal of Spices and Aromatic Crops, 1994)
An in vitro method for propagation of garlic (Allium sativum) via somatic embryogenesis is described. Complete plantlets were obtained by a sequential supply of different basal media and growth hormones. Murashige & Skoog’s medium with kinetin (5.0 ppm) and 2,4- dichlorophenoxy acetic acid (0.5 ppm) promoted embryogenic callus formation. Shoot regeneration was achieved by transferring embryogenic callus to Gamborg’s B, medium with kinetin and indole acetic acid whereas root formation occurred in same basal medium supplemented with a-napthalene acetic acid (0.1 ppm). Sucrose at a higher concentration (10%) had stimulatory effect on shoot regeneration potential of embryoids. A characteristic garlic odour developed in this culture.